Pengetahuan Primipara Tentang Teknik Menyusui yang Baik - Magdalena Limbong; Desriani Desriani (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Influencing factors in the success of breastfeeding are the mother's knowledge of how to breastfeed properly and correctly, which includes the position of the mother and baby's body, the position of the baby's mouth, and the mother's nipples. Purpose: To know the knowledge of primiparous mothers about good breastfeeding techniques. Methods: Descriptive quantitative research relates and interprets data relating to facts, circumstances, and variables as they are. Results: Showed respondents had 86.6% good knowledge and 80% good knowledge. Conclusion: The respondents had a good level of knowledge and breastfeeding techniques. It is hoped that primipara mothers use good breastfeeding techniques and always add insight into science and technology in breastfeeding techniques